Managing territorial conflicts in Georgia: Achilles’ heel of the European Union foreign policy - Makhashvili, Levan (Видавництво Львівської політехніки, 2011)
The 2008 Georgia-Russia war clearly demonstrated the apparent failure of the EU conflict resolution policy in the region. The paper thus investigates why the Union could not resolve the territorial conflicts in Georgia. It draws on data collected using intensive interviews in Tbilisi, Brussels and Prague to reveal what the decision – and policy – makers think of, and the importance they attach to the reasons of the EU failure.
Управління територіальними конфліктами в Грузії: ахіллесова п’ята зовнішньої політики Євросоюзу
Keywords: European Union; conflict resolution; Georgia; Russia; EU instruments; EU decision-making vulnerability; incoherence of EU member states’ positions